Comparison of immediate colposcopy, repeat conventional cytology and high-risk human papillomavirus testing for the clinical management of atypical squamous cells of undetermined significance cytology in routine health services of Medellin, Colombia: The ASCUS-COL trial (2021)
ABSTRACT : In the context of opportunistic cervical cancer screening settings of low-and-middleincome countries, little is known about the benefits of high-risk human papillomavirus (hrHPV) testing on high-grade cervical abnormality detection among women with atypical squamous cells of undetermined significance (ASC-US) cytology in routine clinical practice. We compared the effectiveness of immediate colposcopy (IC), conventional cytology at 6 and 12 months (colposcopy if ≥ASC-US) (RC) and hrHPV testing (colposcopy if hrHPV-positive) (HPV) to detect cervical intraepithelial neoplasia grade 2 or more severe diagnoses (CIN2+) among women aged 20 to 69 years with ASC-US in routine care. Participants (n = 2661) were evenly randomized into three arms (n = 882 IC, n = 890 RC, n = 889 HPV) to receive services by routine healthcare providers and invited to an exit visit 24 months after recruitment. Histopathology was blindly reviewed by a quality-control external panel (QC). The primary endpoint was the first QC-diagnosed CIN2+ or CIN3+ detected during three periods: enrolment (≤6 months for IC and HPV, ≤12 months for RC), follow-up (between enrolment and exit visit) and exit visit. The trial is completed. Colposcopy was done on 88%, 42% and 52% of participants in IC, RC and HPV. Overall, 212 CIN2+ and 52 CIN3+ cases were diagnosed. No differences were observed for CIN2+ detection (P = .821). However, compared to IC, only HPV significantly reduced CIN3+ cases that providers were unable to detect during the 2-year routine follow-up (relative proportion 0.35, 95% CI 0.09-0.87). In this context, hrHPV testing was the most effective and efficient management strategy for women with ASC-US cytology.